(untitled) (Research, Society and Development, 2022)
Objective: to this end, we aimed to describe causes and consequences of iron deficiency anemia in preschool-age children. Method: an integrative literature review study with the LILACS, PUBMED/MEDELINE and SCIELO databases, between 2012 and 2022. 75 articles were identified, 10 of which were used in the elaboration of the work. Results show that iron-deficiency anemia stands out as a serious Public Health problem, being considered the most common of anemias, the high causal potential of iron-deficiency anemia in the child population was evidenced, thus compromising child development. In addition, there are multiple approaches to prevention, control and treatment to prevent children from suffering from these conditions. However, although all forms of prevention are carried out properly, it is not the only causal way, as it is a chronic public health problem in the population’s access to adequate sanitary conditions, which strongly suggests that there is a problem for the cause of this anemic condition.